Video Poetry: the Problem of Subject and Context (Филологический класс, 2021)
The article deals with the problem of correlation between the poetic text and the video footage in modern video poetry. Despite the fact that this topic has already been touched upon in one way or another by researchers of the new direction in media art, not all issues have been resolved. Examples from the archive of the Fifth Leg video poetry festival (organized by E. Troepolskaya and A. Rodionov) are used for discussion in this article. The study considers the following types of video poetry: a video record of the author's reading; a video illustration or video clip based on a poem; a footage presented as a new interpretation, or as a “secondary” text, created on the basis of the “primary” one; a video production which initially, at the stage of planning already, combines poetic and visual components. Modern video poetry at a new stage in cultural history continues the idea of Gesamtkunstwerk, which inspired romantics (Goethe, Byron, Wagner) and symbolists, as well as the verbal-visual experiments of avant-garde artists. In contrast to the art of romanticism and “high” modernism, video poetry is democratic and in the form of its online existence it opposes the art market and enjoys a certain freedom of self-expression. In general, video poetry can be considered one of the new reading practices that are attractive to the generation of visuals. At the same time, video poetry faces difficulties due to the differences between the languages of the verbal and visual forms of art. The verbal characteristic does not pretend to be understood literally, and the visual “subtitles” only simplify the content of the poem. The language of poetry is metaphorical; therefore, the footing should be highly semiotic. The solution to the problem of the embodiment of the lyrical subject is also difficult: expressed in the text, as a rule, by a pronoun, the lyrical subject can hardly be visually substituted for by a concrete character of the video footage. Finally, a special problem is associated with the relationship between the poetic rhythm and video editing. Variants of the solution of the above mentioned issues in the videos of R. Osminkin (the poem “Life Passes By”), O. Yagodin (the poem by Mandelstam “Cinematograph”), A. Tolkacheva (“Fragments of Disappearance”) are considered in this article. Concrete examples convince us that there should be a “gap” between the verbal and visual components in video poetry, and that a new meaning arises as a result of experiments precisely on the borderline between literature and cinema. The key methods for visualizing a poem include the dissimilarity of the subject of the lyric expression and the change of the cultural context.